ANALISIS BROWNING BUAH PISANG KEPOK (Musa paradisiaca L.) SETELAH PERLAKUAN ASAM ASKORBAT DAN LIDAH BUAYA (Aloe barbadensis L.) - Ratri Mauluti Larasati; Martha Lulus Lande; Zulkifli Zulkifli; Sri Wahyuningsih (Jurnal Penelitian Pertanian Terapan, 2019)
Fruit is a necessity for most Indonesian people. Kepok banana is a climacteric fruit that can experience browning quickly. Therefore, this study was conducted to find a safe and effective material to prevent the browning process of kepok bananas. This study aims to determine the differences in the browning index, and the activity of the enzyme dehydrogenase in kepok banana cells. This study was conducted using a 2x3 factorial design. Factor A is ascorbic acid with 2 concentration levels namely 0% (b / v) and 5% (b / v). Factor B is Aloe (Aloebarbadensis L.) leaf extract with 3 levels, namely 0%, 5%, and 10%. The quantitativeÂ parameters are browning index and total dissolved carbohydrate content. The qualitative parameter is dehydrogenase enzyme activity. Levene test and variance analysis were carried out with 5% real level. The results obtained were kepok bananas with treatments coloured brighter than control. Ascorbic acid and Aloe (Aloe barbadensis L.) affect the browning index and dissolved total carbohydrate content of the sample. A decrease in dehydrogenase enzyme activity happened in the ascorbic acid treatment. Conclusions obtained from the study are ascorbic acid with a concentration of 5% can reduce the browning index of kepok banana by 31%, ascorbic acid with a concentration of 5% can maintain total dissolved carbohydrate content kepok banana as much as 53%, and Aloe extract 10% retain total dissolved carbohydrate content sample is 20%.